Key factors for information integration in the supply chain – measurement, technology and information characteristics - Szymczak, Maciej; Ryciuk, Urszula; Leończuk, Dorota; Piotrowicz, Wojciech; Witkowski, Krzysztof; Nazarko, Joanicjusz; Jakuszewicz, Joanna (Journal of Business Economics and Management, 2018)
This paper aims to identify key factors related to information management and integration in the supply chain (SC). The initial set of factors was identified in the literature, namely, information quality and content, performance metrics, and information technologies. The construct was then tested empirically using the sample of 200 Polish companies. Computer-Assisted Telephone Interviews (CATI) were based on a structured questionnaire, then, data exploratory factor analysis (EFA) was performed. The conducted EFA determined four main factors for information management and integration in the supply chain that should be considered, namely, information characteristics, ICT used in information management, the scope of information and shared performance metrics. Results confirmed the importance of some of the factors related to information management in the supply chain, however having a different set of variables than indicated in the literature. Additionally, research introduced new factors, namely, information characteristics and the scope of shared information, instead of information quality and information content. Moreover, findings suggested that the key role in SC information integration was related to established technologies, focused on transport, customer, and ERP management, while emerging technologies, such as cloud computing and data mining were not of the top importance among the surveyed companies.